2015
DOI: 10.1002/jmri.24943
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of quantitative susceptibility mapping in the brain at two field strengths from two vendors

Abstract: Purpose To assess the reproducibility of brain quantitative susceptibility mapping (QSM) in healthy subjects and in patients with multiple sclerosis (MS) on 1.5 and 3T scanners from two vendors. Materials and Methods Ten healthy volunteers and 10 patients were scanned twice on a 3T scanner from one vendor. The healthy volunteers were also scanned on a 1.5T scanner from the same vendor and on a 3T scanner from a second vendor. Similar imaging parameters were used for all scans. QSM images were reconstructed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
119
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 99 publications
(129 citation statements)
references
References 40 publications
(71 reference statements)
10
119
0
Order By: Relevance
“…Differences in the age dependency of substantia nigra susceptibility have also been reported between L1 and L2 regularizations (Bilgic et al, 2012). A recent publication (Deh et al 2015) has shown good overall reproducibility in QSM using the algorithm employed in this study however, and such limitations should not be crucial.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Differences in the age dependency of substantia nigra susceptibility have also been reported between L1 and L2 regularizations (Bilgic et al, 2012). A recent publication (Deh et al 2015) has shown good overall reproducibility in QSM using the algorithm employed in this study however, and such limitations should not be crucial.…”
Section: Discussionmentioning
confidence: 80%
“…Cross-sectional design relies on age-related differences between persons that are captured in a snapshot frozen in time, and cannot measure the true dynamic trajectories within a person. As in vivo imaging of susceptibility is improving and already shows good between scan reliability (Deh et al, 2015), repeated measures design becomes feasible.…”
Section: Discussionmentioning
confidence: 99%
“…QSM of biometals has been valuable in studying disease processes. QSM is shown to be reproducible across scanner makers, models, field strengths, and sites (37-40). QSM can be automated, making it ready for wide dissemination to evaluate its diagnostic and therapeutic value in clinical practice.…”
Section: Introductionmentioning
confidence: 96%
“…It also less strongly depends on data-acquisition sequence (Sun and Wilman, 2015) and parameters and should be better reproducible across scanners from different manufacturers and field strengths (Deh et al, 2015).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…It can be speculated that fQSM and QSM may prove particularly useful, e.g., in future studies with an interest in layer-specific functional information (Koopmans et al, 2011), in attempts to focus on vascular components and venography of neuronally activated regions, or quantification of tissue oxygenation (Özbay et al, 2015b) and cerebral metabolic rate of oxygen consumption (Zhang et al, 2015). Such studies may also benefit from the recent achievements in accelerating the QSM processing Langkammer et al, 2015).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%